Home learning environment in early years and Greek parents’ socio-demographics - Karavida, Vasiliki; Tympa, Eleni; Nefeloudi, Evmorfia (Institute of Advanced Engineering and Science, 2024)
The home learning environment (HLE) is the first environment in which children’s early learning takes place. A number of studies have provided empirical evidence that the HLE contributes to children's cognitive, socio-emotional development. This study addresses the question of the factors that can be associated with creating a positive learning environment for children at home. Pilot quantitative data was collected from 324 families through a questionnaire about the activities parents get involved with their children. The frequency of reading-related activities as well as other in-home and out-of-home learning activities was calculated. Pearson’s correlation coefficient was employed to assess the relationship between parent education levels and activities within the HLE. Questionnaire reliability was examined using Cronbach’s alpha coefficient. The results showed that the gender and educational level of parents had no influence on the frequency of their involvement in the activities or the type of activities they chose to engage. However, the parents’ educational level has an impact on their beliefs, which influence the provision of learning opportunities and the quantity and quality of parent-child interactions. Further research on parental guidance or children's academic performance could collect more information on the factors that can create a more stimulating HLE.